Extended object languages for the extolware persistence framework - Ming, Lim Tong; Lee, Sai Peck (2004)
Users interact with a database system through a set of database languages and this makes designing database languages a very challenging task to a computer software engineer. A set of welldefined database languages must be easy to learn, easy to understand and powerful enough to capture semantic of a problem domain. This paper discusses design issues of a proposed database language, namely Extended Object Language or EOL for short, for an Extolware Persistent Object framework (Lim & Lee, 1997, 1998, 1999, 2001, 2002a, 2002b, 2002c) that provide wrapping services for relational database systems and multidimensional database systems (DataPro, 1996; IBM Corp., 2001; Informix Software Inc., 2001a, 2001b). This research examines SQL3 (Fortier, 1999) and ODL/OQL (Cattell & Barry, 1999) with an overview of their language constructs and operators that support object-oriented requirements as stated in Object Data Management Group (ODMG) object model. Next, a discussion on the Extended Object Language (EOL) and its language constructs are examined. This is followed by a close examination of new database operators and constructs introduced into EOL. A design overview and evaluation of these database languages are examined. A summary on these languages is presented at the end of the paper with conclusion and further research plans.